Religious Aspects of the Film “The Story of the Prophet Eliasz of Wierszalin” by Krzysztof Wojciechowski - Sokołowski, Marek (Studia Warmińskie, 2021)
The article is an attempt to determine whether in the history of world cinema there is a separate film genre that can be termed as religious cinema or whether there are only features with religious and sacred themes. Based on the analysis of the groundbreaking cinematographic works, the article explores this subject. The author of the study directs his attention to a film that falls within the stream of religious cinema. It is the film Story of a Prophet Elijah from Wierszalin, is a fictionalized biographical story about Elijah, an Orthodox prophet from Podlasie, the founder of the sect of Grzybowszczyzna.